2007
DOI: 10.1002/pam.20285
|View full text |Cite
|
Sign up to set email alerts
|

The stigma of public programs: Does a separate S‐CHIP program reduce it?

Abstract: Previous studies suggest access to and satisfaction with care may be different for enrollees in S-CHIP and Medicaid, but it is unclear whether those differences are fully explained by socioeconomic characteristics of the enrollees. We analyze access and satisfaction of three groups of children: Medicaid enrolled, S-CHIP enrolled, and children who are income eligible for Medicaid but carry a card similar to the state's S-CHIP children's card. Both enrollees and providers may believe that these children are enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 15 publications
(14 reference statements)
0
19
0
Order By: Relevance
“…As is shown in Ketsche et al (2007a) there is some stigma associated with Medicaid enrollment in Georgia relative to enrollment in the PeachCare program, which is perceived to be more like a private health plan. PeachCare premium increases may reinforce this perception and thus increase the stigma associated with Medicaid enrollment.…”
Section: Premium Changesmentioning
confidence: 87%
“…As is shown in Ketsche et al (2007a) there is some stigma associated with Medicaid enrollment in Georgia relative to enrollment in the PeachCare program, which is perceived to be more like a private health plan. PeachCare premium increases may reinforce this perception and thus increase the stigma associated with Medicaid enrollment.…”
Section: Premium Changesmentioning
confidence: 87%
“…The magnitude of the effects may be small for several reasons; the availability of charity care has been shown to reduce the demand for health insurance and increase the likelihood of being uninsured, especially among the low-income population (Herring 2005;Rask and Rask 2000). Additionally, information and administrative costs, along with the perceived stigma and reputation of public insurance, have been shown to be important barriers to enrollment in public insurance programs (Aizer 2007;Ketsche et al 2007). …”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…The magnitude of the effects found in this study may be small for several reasons; the availability of charity care has been shown to reduce the demand for health insurance and increase the likelihood of being uninsured, especially among the low-income population (Rask and Rask 2000;Herring 2005). Additionally, information and administrative costs, along with the perceived stigma and reputation of public insurance have been shown to be important barriers to enrollment in public insurance programs (Aizer 2007;Ketsche et al 2007).…”
Section: Discussionmentioning
confidence: 99%